Dynamic Memory Allocation - wason, Saksham; kumar, piyush; rathi, shubham (IJRDO -Journal of Computer Science Engineering, 2017)
Memory management is an important part of modern computer system. Dynamic Memory Allocation has plays very important role in Memory Management and becomes fundamental part of today’s computer system. It is classical problem in computer science by paying some complexity. It is minimizing the cost of memory by providing efficient use of it and it is art of handling computer memory powerfully. Memory Management is commonly one of the most critical parts of Operating System, especially the main memory. In this paper, we will describe the role of Dynamic Memory allocation in Memory Management, comparison with static memory allocation, and issues with using DMA